FRI0058 Improvements in Health Related Quality of Life (HRQOL) Reported by Rheumatoid Arthritis (RA) Patients in a Randomized Controlled Trial [RCT] of Sarilumab [Mobility] that Met or Exceeded the Patient Acceptable Symptom State [Pass] And Normative Values. (9th June 2015) - Strand, V.; Kosinski, M.; Joseph, G.; Chen, C.; Van Hoogstraten, H.; Graham, N.; Huizenga, T.; Genovese, M.C.
Abstract : Background: Clinical and patient reported outcomes provide complimentary information about the efficacy of treatment in RCTs in RA. Linking these two may improve our understanding of treatment benefit. The MOBILITY intent-to-treat population included 1, 197 patients randomized 1:1:1 to placebo+MTX, sarilumab 150mg every two weeks (q2w) +MTX or 200mg q2w+MTX. Most common TEAEs included infections and injection site reactions. A higher incidence of serious infections was observed with sarilumab 1 . Objectives: To evaluate reported improvements in HRQoL by ACR20 responders in this phase 3 RCT. Methods: HRQoL was measured using the SF-36v2; fatigue by FACIT-Fatigue. Only ACR20 responders were included, since there were few ACR50 responders in the placebo group and no differences in baseline characteristics of responders between treatment groups. At wk 24, we calculated the percentage of ACR20 responders that met or exceeded: 1) PASS 2, 3, a state of well-being which patients consider to be satisfactory, in 6 SF-36v2 domains; 2) general population normative values for SF-36v2 and FACIT-Fatigue scores. Differences from placebo were tested for statistical significance (p<0.05) by Chi-square. Results: ACR20 responses were 33.5% in placebo, 58.4% in 150mg and 66.4% in 200mg sarilumab groups. The percentages of responders in both 150mg and 200mg sarilumab groups with scores ≥PASS at wk 24 exceeded placebo across all 6 SF-36 domains; statistically significant for physical functioning, vitality, social functioning and mental health domains. For example, 82.7% (150mg) and 87.6% (200mg) sarilumab patients reported improvements ≥PASS in SF-36v2 vitality domain vs 72.7% placebo. The percentages of responders receiving 150mg and 200mg sarilumab with scores ≥normative values at wk 24 exceeded placebo across all SF-36v2 domains and FACIT; statistically significant for SF-36v2 bodily pain, vitality, mental health domains; mental component summary score and FACIT. For example, 46.3% (150mg) and 54% (200mg) of sarilumab patients reported scores ≥normative values in SF-36v2 vitality domain vs 38.6% placebo. Similar findings were observed at wk 52. Conclusions: Among ACR20 responders, those receiving sarilumab+MTX reported better HRQoL than with placebo+MTX, particularly in measures of bodily pain, vitality, and fatigue by SF-36 and FACIT. Largest percentage differences vs placebo were observed based on scores attaining normative values, which were more discriminative for the Sarilumab 200mg dose than PASS. Observed differences may be driven in part by more high level responders in the active treatment groups. References: Genovese M et al. Abstr. EULAR14-SCIE-3001, EULAR 2014 Heiberg T et al. Ann Rheum Dis 2008;67:967-971 Strand V et al. J Rheumatol. 2011;38(8):1720-1727 Acknowledgements: The study was sponsored by Sanofi and Regeneron Pharmaceuticals Inc. Editorial support was provided by Jennifer Dunphy of Optum and was funded by Sanofi and Regeneron Pharmaceuticals Inc. Disclosure of Interest: V. Strand Consultant for: AbbVie, Afferent, Amgen, Biogen Idec, Bioventus, BMS, Carbylan, Celgene, Celltrion, Consortium of Rheumatology Researchers of North America (CORRONA), Crescendo, Genentech/Roche, GSK, Hospira, Iroko, Janssen, Lilly, Merck, Novartis, Pfizer, Regeneron, Sanofi, SKK, Takeda, UCB, Vertex, M. Kosinski Consultant for: Sanofi, Regeneron, G. Joseph Shareholder of: Amgen Inc, Pfizer Inc., Employee of: Sanofi, C. Chen Employee of: Regeneron Pharmaceuticals, H. Van Hoogstraten Employee of: Sanofi, N. Graham Shareholder of: Regeneron Pharmaceuticals, Employee of: Regeneron Pharmaceuticals, T. Huizenga Consultant for: Merck, UCB, Bristol Myers Squibb, Biotest AG, Pfizer, Novartis, Roche, Sanofi-Aventis, Abbott, Crescendo Bioscience, Nycomed, Boeringher, Takeda, Zydus, and Eli Lilly, Speakers bureau: Merck, UCB, Bristol Myers Squibb, Biotest AG, Pfizer, Novartis, Roche, Sanofi-Aventis, Abbott, Crescendo Bioscience, Nycomed, Boeringher, Takeda, Zydus, and Eli Lilly, M. Genovese Grant/research support from: Sanofi, Regeneron Pharmaceuticals, Eli Lilly, Consultant for: Sanofi, Regeneron Pharmaceuticals, Eli Lilly